Зовнішні витрати від забруднення при виробництві електроенергії як індикатор стійких електрогенеруючих систем - Matsuki, Y.; Brondzia, О.; Maslukivska, O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
This research applies the Impact Pathway Approach [1] for identifying the external cost for the fossil-fuel electricity production in Ukraine. Using the SimPact Computer Code and Willingness to Pay survey, it calculates the external costs of the morbidity and mortality of population due to the air pollutants emitted from an electricity generation plant using as an example Triypilska Electric Power Generation Plant in Ukrainka town. Based on the research results there were made recommendations to include the external costs into the price of electricity in Ukraine generated from the fossil fuel combustion.